2023
DOI: 10.1186/s12879-023-08155-6
|View full text |Cite
|
Sign up to set email alerts
|

Decentralization of viral load testing to improve HIV care and treatment cascade in rural Tanzania: observational study from the Kilombero and Ulanga Antiretroviral Cohort

Abstract: Introduction Monitoring HIV viral load (HVL) in people living with HIV (PLHIV) on antiretroviral therapy (ART) is recommended by the World Health Organization. Implementation of HVL testing programs have been affected by logistic and organizational challenges. Here we describe the HVL monitoring cascade in a rural setting in Tanzania and compare turnaround times (TAT) between an on-site and a referral laboratory. Methods In a nested study of the pr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…The high percentage of coverage could be attributed to country strategies of free HIV care and treatment services including consultation, testing, medications, and follow-up. We found a system sensitivity of 84.4%; this could be attributed to six multi-month dispensing (6MMD) in the country that delayed the eligible clients from taking HVL samples for testing, which started in 2022 (5). Regardless the challenge noted, it has been reported that giving stable customers multi-month dispensing (MMD) of ARV improves health outcomes in terms of immunosuppression, viral suppression, retention, mortality, and adherence (13–15).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The high percentage of coverage could be attributed to country strategies of free HIV care and treatment services including consultation, testing, medications, and follow-up. We found a system sensitivity of 84.4%; this could be attributed to six multi-month dispensing (6MMD) in the country that delayed the eligible clients from taking HVL samples for testing, which started in 2022 (5). Regardless the challenge noted, it has been reported that giving stable customers multi-month dispensing (MMD) of ARV improves health outcomes in terms of immunosuppression, viral suppression, retention, mortality, and adherence (13–15).…”
Section: Discussionmentioning
confidence: 99%
“…HVL testing and monitoring has complex technical and logistic requirements requiring continuous expert guidance and a reliable quality management system. Some countries, including Tanzania, have adopted a hub-and-spoke model coupled with clustering clinics and efficient specimen collection, transportation and referral systems (5).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, taking the initiative for baseline VL testing for HIV-positive clients starting ART may be required to properly monitor ART adherence from the start and optimize the benefits of HIV care and treatment programs. Furthermore, cost-effective, affordable, rapid, and decentralized VL testing might increase the uptake of baseline VL and viral suppression in general [ 26 , 50 , 51 ]. Moreover, considering pretreatment HIV drug resistance genotypic testing at baseline could be helpful in identifying patients at a higher risk of virological failure and contribute to the long-term success of viral suppression [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is available as a once-daily dosing for HIV patients, has a high genetic barrier to resistance, and is safer than non-DTG-based cART [ 25 ]. However, there were limited data on baseline VL testing before the initiation of ART in LMICs, including Ethiopia, because of its rigorous laboratory work, long turnaround times, and lack of adequate infrastructure and supplies [ 26 ]. Furthermore, since the rollout of DTG-based regimens as first-line ART in Ethiopia, no study has linked baseline factors, including the VL test, with virological non-suppression after six months of follow-up on ART.…”
Section: Introductionmentioning
confidence: 99%